The complete chloroplast genome sequence of Korean Lonicera japonica and intra-species diversity - Kang, Shin-Jae (Mitochondrial DNA B Resour, 2018)
Lonicera japonica is a traditional medicinal plant well known for its anti-inflammatory effect. The complete chloroplast genome sequence of L. japonica collected from Korea was obtained by de novo assembly using whole genome sequence data. The chloroplast genome is 155,060 bp in length, containing 88,853 bp in a large single copy (LSC), 18,653 bp in a small single copy (SSC) and 23,777 bp in a pair of inverted repeats (IRs). A total of 112 genes including 78 protein-coding genes and 34 structural RNA genes were identified. The sequence comparison of two L. japonica collected from Korea and China revealed 48 single nucleotide polymorphisms (SNPs) and 45 insertions/deletions (InDels). In addition, phylogenetic analysis represented intraspecific diversity within L. japonica species collected in Korea and China.